Koncepcja organizacji multiprojektowej w branży TSL - Dziekoński, Krzysztof; Jurczuk, Arkadiusz (Idea of Multiproject Logistic Company, 2008)
The increase in competitiveness and price pressure results in increasing number of overseas localizations where the cost of production is the lowest. That trend puts more attention to the process of global distribution. The authors present an idea of logistic company operating in the global supply chain. The idea of managing such a company through logistic projects is also introduced. In the paper the idea of a logistic enterprise operating in 3PL (Third Party Logistics) frame is presented. Those companies are an exhibit of enterprises that need to be managed in a multiproject environment.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 256-263